Akomodasi Komunikasi Antar Budaya Pengurus Ponpes Ngalah dengan Santri Luar Jawa dalam Membangun Intimate Relationship - Rochman, M Fatchur; Yuwita, Nurma (AGUNA: Jurnal Ilmu Komunikasi, 2025)
Intercultural interactions between administrators and students from outside Java at the Ngalah Purwosari Islamic Boarding School often occur. Cultural differences between them lead to variations in communication behavior. This research aims to describe intercultural communication and the obstacles that arise at the Ngalah Purwosari Islamic Boarding School. This research is a qualitative field study, carried out at this location using data collection techniques through observation, interviews and documentation. Research findings show that intercultural communication patterns include processes of cultural adaptation, mutual respect, and repetition of communication. Communication accommodation at the Ngalah Islamic Boarding School involves convergence, divergence and excessive accommodation. This research provides an overview and evaluation to the administrators of the Ngalah Islamic Boarding School regarding the importance of effective communication in managing cultural diversity, as well as providing recommendations for future research in the same field.